A case of thyrotoxicosis following peripheral blood stem cell transplantation - Omar, Ahmad Marzuki; Shahar, Mohammad Arif; Wan Seman, Wan Juani; M., Azura Dina; Rajoo, Subashini; Ooi, Chew Peng; Loh, Huai Heng; Omar, Mohd Rahman; A Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (ASEAN Federation of Endocrine Societies, 2015)
Thyroid dysfunction may occur in patients after haematopoietic stem cell transplantation. We report a 41-year-old gentleman who was investigated for bicytopenia in June 2012 after presenting with pruritus and gum bleeding. His initial bone marrow aspiration (BMA) showed features of thrombocytopenia, which persisted despite treatment with oral steroid. A repeat BMA a year later revealed hypocellular marrow with full blood pictures showed persistent bicytopenia with presence of blast cells. Acute myeloid leukaemia was later confirmed with subsequent BMA. First induction/consolidation chemotherapy was performed in September 2013. He had persistent disease despite reinduction chemotherapy 6 weeks later. He underwent allogeneic peripheral blood stem cell transplantation (PBSCT) in March 2014. His donor was his brother who has had no significant medical problems including thyroid disease. The transplantation was complicated by neutropenic sepsis, which later resolved. Three weeks post transplantation he was noted to have suppressed thyroid-stimulating hormone levels with elevated free thyroxine levels and upper limit of free T3 (TSH <0.001 uIU/ml, fT4 24.59 pmol/l, fT3 4.1 pmol/l). His TSH a month before transplantation was 0.27 uIU/ml. However, his free T4 dan T3 levels were not available. He was otherwise asymptomatic. His thyroid antibodies later were found to be normal (anti-thyroglobulin, ATG <20 IU/ml; anti-thyroid peroxidase, anti-TPO 15.8 IU/ml). As he remained asymptomatic of thyrotoxicosis, he chose not to be treated medically and was given a follow-up in the clinic. This case illustrates the possible thyroid dysfunction following haematopoietic stem cell transplantation, which may or may not related to autoimmunity. Autoimmune thyroid disease (AITD) is a recognised complication of autologous or allogeneic haematopoietic stem cell transplantation (HSCT). In a series, 10 cases of autoimmune thyroid disease were diagnosed among 721 HSCT recipients, with three having features of hypothyroidism, five had hyperthyroidism and two had sequential hypo- and hyperthyroidism. Significant risk factors included HSCT for chronic myeloid leukaemia, HLA B46 and DR9 loci, the A2B46DR9 haplotype and female donors. Prior to the series, there were 17 reported cases of AITD after allogeneic HSCT (12 had hyperthyroidism, 5 had hypothyroidism).